ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN MOBILE BANKING PADA PERUSAHAAN PERBANKAN DI INDONESIA - Umi Pratiwi; Muhammad Nur (Universitas Semarang, 2020)
This research is the experimental hypothesis test by using the empirical study method. The observed period of financial reports are four years before and after the implementation of mobile banking. The analysis of this researched was used paired sample t-test and comparative analysis.The result of this researched showed that operational expense to the operational revenue ratio detected have the significant differences and actually showed there is positive growth after implementation of mobile banking compare with before implementation of mobile banking. And then LDR detected have the significant differences and it turned out that showed there is negative growth after implementation of mobile banking compare with before implementation of mobile banking. Meanwhile CAR, fulfillment elimination of remission productive assets ratio, and ROA detected do not have the significant differences but already showed there is positive growth after implementation of mobile banking compare with before implementationof mobile bankingKeywords: capital adequacy ratio (CAR), fulfillment elimination of remission productive assets ratio, return on asset ratio (ROA), operational expense to the operational revenue ratio, and loan to deposit ratio (LDR)